1990
DOI: 10.1002/ajim.4700180508
|View full text |Cite
|
Sign up to set email alerts
|

Biological monitoring of a worker acutely exposed to MBOCA

Abstract: A 30 year-old male polyurethane worker was exposed to an accidental spill of 4,4'-methylene-bis-2-chloroaniline (MBOCA) at a plant producing MBOCA-cured plastic products. Exposure to MBOCA is significant in that this compound is a known animal carcinogen and a suspected human carcinogen. The employee was sprayed over his upper body and extremities with molten MBOCA while cleaning out a clogged hose from a MBOCA and polymer mixing machine. The subsequent environmental and medical evaluation of this episode incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 16 publications
1
5
0
2
Order By: Relevance
“…The close correlation observed between``total'' MOCA and``free'' MOCA in urine samples of 40 workers was also noted by Osorio et al (1990) in the urine of one worker sprayed accidentally over his upper body and limbs with molten MOCA; in this case, they reported a lower free/total MOCA ratio than us (35% vs 55%). Using our protocol to thaw frozen urine samples, we observed that on a few of the samples that had been previously analysed, then left at A20°C for several months and reanalysed, there was a 64% mean increase in the apparent MOCA concentration.…”
Section: Urinary Moca Markerssupporting
confidence: 77%
See 2 more Smart Citations
“…The close correlation observed between``total'' MOCA and``free'' MOCA in urine samples of 40 workers was also noted by Osorio et al (1990) in the urine of one worker sprayed accidentally over his upper body and limbs with molten MOCA; in this case, they reported a lower free/total MOCA ratio than us (35% vs 55%). Using our protocol to thaw frozen urine samples, we observed that on a few of the samples that had been previously analysed, then left at A20°C for several months and reanalysed, there was a 64% mean increase in the apparent MOCA concentration.…”
Section: Urinary Moca Markerssupporting
confidence: 77%
“…In addition, the heating of urine samples does not take account of the acetylated metabolites of MOCA, and``heat-labile'' MOCA is a more suitable de®nition Jedrzejczak and Gaind 1992;Wu et al 1996). Finally, the term``total'' MOCA should be employed when the urine samples are hydrolysed under strong acid or alkaline conditions (McKerrell et al 1987;Osorio et al 1990). …”
Section: Urinary Moca Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…Urine samples obtained by Ward et al (1990) from plant workers several months after production ceased also showed detectable MBOCA levels that ranged as high as 50,000 μg/L. Osorio et al (1990) reported a urine MBOCA level of 1,700 μg/L 4 hr postexposure in a worker who was accidentally sprayed with molten MBOCA, but no acute symptoms or other laboratory abnormalities were observed. The urine MBOCA levels in the MBOCA-manufacturing factory workers were much higher than in workers at a polyurethane elastomer factory using MBOCA as a curing agent.…”
Section: Discussionmentioning
confidence: 94%
“…The acute health effects of exposure to MbOCA include irritation and a burning sensation to the skin and eyes, nausea, and gastrointestinal and renal effects 5) . Animal studies have shown that chronic exposure to MbOCA can cause bladder cancer 6 , 7) .…”
Section: Introductionmentioning
confidence: 99%